2007
DOI: 10.1016/j.drugalcdep.2006.12.013
|View full text |Cite
|
Sign up to set email alerts
|

Cannabis use and cannabis use disorders and their relationship to mental disorders: A 10-year prospective-longitudinal community study in adolescents

Abstract: A range of psychopathological conditions, including depressive, bipolar and less consistently anxiety disorders as well as the degree of their comorbidity are significantly associated with incident CU and progression to CUD, even when controlling for externalising disorders. A better understanding of this complex interplay may result in better aetiological models and intervention strategies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
197
1
5

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 273 publications
(216 citation statements)
references
References 39 publications
13
197
1
5
Order By: Relevance
“…Moreover, specific manifest outcomes in Fig. 1 may be linked to more than one psychopathology spectrum ; for example, marijuana use and problems may show additional connections with the internalizing spectrum (Wittchen et al 2007) and different elements of impulsivity may be associated with specific risky behaviors (Smith et al 2007).…”
Section: Co-morbidity Patterns For Dsm Disordersmentioning
confidence: 99%
“…Moreover, specific manifest outcomes in Fig. 1 may be linked to more than one psychopathology spectrum ; for example, marijuana use and problems may show additional connections with the internalizing spectrum (Wittchen et al 2007) and different elements of impulsivity may be associated with specific risky behaviors (Smith et al 2007).…”
Section: Co-morbidity Patterns For Dsm Disordersmentioning
confidence: 99%
“…We considered several individual, peer and family factors. When searching for relevant literature on illicit drugs we focused on cannabis, as in Finland, like in many developed countries, cannabis products (marijuana, hashish) are the most commonly used ones (Programme on Substance Abuse, 1997; Virtanen and Sjöberg, 2006 (Guxens et al, 2007a(Guxens et al, , 2007bKandel and Yamaguchi, 1993), especially age of onset (Gilvarry, 2000;Vega and Gil, 2005), alcohol consumption (Guxens et al, 2007a(Guxens et al, , 2007b, especially drinking to intoxication Wittchen et al, 2007). Own ever smoking was asked prospectively at the age 14 survey.…”
Section: Predictors-mentioning
confidence: 99%
“…Among individual factors, use of licit substances Gilvarry, 2000;Guxens et al, 2007aGuxens et al, , 2007bKandel and Yamaguchi, 1993;Vega and Gil, 2005;Wittchen et al, 2007) has been reported consistently as a risk factor for subsequent use of illicit drugs. Characteristics related broadly to externalizing behaviors, such as impulsivity (Conway et al, 2003), early behavior problems (Kreek et al, 2005), as well as behavioral and emotional symptoms (Brook et al, 1996;Buckner et al, 2008;Jane-Llopis and Matytsina, 2006;Monshouwer et al, 2006;White et al, 2001;Wittchen et al, 2007) have been identified as risk factors for drug use.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Use of other drugs has been related to both mental health problems and cannabis use or dependence, and attenuates these associations [5,7,[23][24][25][26]. This is also true for childhood adversities [27,28].…”
Section: Introductionmentioning
confidence: 97%